Managing Overweight and Obesity in Ghana from a Cultural Lens: The Complementary Role of Behaviour Modification - Jnr. John Elvis Hagan; Christiana Nsiah-Asamoah,; Thomas Hormenu,; Dietmar Pollmann,; Thomas Schack, (Journal of Preventive Medicine And Care, 2018)
Extant epidemiological and social diagnosis information shows an alarming upsurge in the prevalence of overweight and obesity over the last decade in developing countries including Ghana. Despite literature on the dangers and associated risk factors of these two health related constructs is well-written and documented, there seems to be a distinct knowledge gap on cultural influences that may trigger the onset of overweight and obesity, and related comorbidities. This review paper provides a general overview on overweight and obesity, and presents a supportive evidence of their rising prevalence as well as associated overall implications on public health in Ghana. Additionally, the paper explores how indigenous cultural perceptions, beliefs and norms impact on dietary and physical activity behaviours of the people. Based on available evidence, the complementary role of behaviour modification towards the management of overweight and obesity is suggested. The PEN-3 model as an appropriate cultural framework is proposed for future empirical investigations. This would afford programme planners to assess how to design culturally underpinned appropriate intervention programmes that would positively influence long term behavioural practices of the local people.
Keywords: Overweight